Analysis of Coliform Bacteria Contamination in Drinking Water Sources in Malang City - Syamsussabri, Muhamad; Ningtyas, Riza Nurhermi; Najah, Amalia Ainun; Fahmi, M. Saiful; Suarsini, Endang (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2018)
This study aims to determine the contamination of coliform bacteria in drinking water sources of residents in Malang City. Type of this research is explorative descriptive research. The study population was all drinking water sources of residents throughout Malang City, while the research sample was 15 residents wells in five subdistricts of Malang City with each sample taken three sample points. The samples were tested using 3M petrifilm E. coli/coliform count plate. The results showed that all the samples studied were contaminated with coliform bacteria with the highest percentage of 23.01% for E. coli bacteria contamination and 15.41% for total coliform bacterial contamination with an average of bacterial colonies 200 colonies.